A rapid method to reduce drug interferences for antibody measurements in pegunigalsidase alfa-treated patients with Fabry disease - Lenders, Malte; Rudolph, Elisa; Rudnicki, Michael; Cybulla, Markus; Brand, Eva (Frontiers in Immunology, 2026)
AimNeutralizing anti-drug antibodies (ADA) limit therapy efficacies significantly. Pegunigalsidase alfa is a newly approved drug for the treatment of Fabry disease. The increased plasma half-life due to PEGylation interferes with ADA measurements including ELISAs and serum-mediated inhibition assays. We developed a rapid protocol eliminating pegunigalsidase alfa from blood samples, without interfering downstream applications.MethodsA rapid protocol based on alkaline-pretreatment followed by acid-based neutralization of agalsidase-spiked control sera was established. Results were confirmed using serum samples from patients with and without neutralizing ADAs drawn during infusions. Repeated ADA measurements including serum-mediated inhibition assays and ELISA-based immunoglobulin isotyping (IgG, IgA, IgM) were performed with sera from 17 patients receiving pegunigalsidase alfa.ResultsAlkaline pretreatment with NaOH was sufficient to eliminate up to 1 µg/ml agalsidase alfa or pegunigalsidase alfa in control sera. AGAL activities in sera drawn during infusions were completely suppressed without interfering subsequent serum-mediated inhibition assays. Based on this method, in one patient a de novo formation of ADAs against pegunigalsidase alfa was identified. Immunoglobulin isotyping showed mainly IgM antibodies towards pegunigalsidase alfa, recognizing PEG moieties and amino acids in this patient. Although his ADAs had a low inhibitory capacity, Western blot analyses demonstrated that the reduced pharmacokinetics might be linked to leucocyte-mediated enzyme elimination. A second patient with pre-existing ADAs before pegunigalsidase alfa-initiation showed a massive induction of anti-PEG antibodies with inhibitory function.ConclusionWe present a rapid alkaline-treatment based method to overcome drug interferences to measure at least free antibodies in patients treated with pegunigalsidase alfa.